2019
DOI: 10.1177/1754073919868762
|View full text |Cite
|
Sign up to set email alerts
|

Does Blocking Facial Feedback Via Botulinum Toxin Injections Decrease Depression? A Critical Review and Meta-Analysis

Abstract: Researchers have proposed that blocking facial feedback via glabellar-region botulinum toxin injections (GBTX) can reduce depression. Random-effects meta-analyses of studies that administered GBTX to individuals with depression indicate that, 6 weeks postintervention, GBTX groups were significantly less depressed compared to placebo groups ( d = 0.83) and pretreatment levels ( d = 1.57). However, we noted the following concerns: (a) effect sizes were extraordinarily large, (b) authors failed to provide informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 111 publications
1
14
0
5
Order By: Relevance
“…Our work expands on two previous meta-analyses by Coles et al (2019) and Parsaik et al (2016). Parsaik et al included the three small RCTs available at the time and reported that the mean difference in depression scores between onabotulinumtoxinA and placebo was as large as -9.80 points difference of rating scales (95% CI -12.90 to -6.69).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Our work expands on two previous meta-analyses by Coles et al (2019) and Parsaik et al (2016). Parsaik et al included the three small RCTs available at the time and reported that the mean difference in depression scores between onabotulinumtoxinA and placebo was as large as -9.80 points difference of rating scales (95% CI -12.90 to -6.69).…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, it is possible that patients who continued in the study were also those who benefitted from the intervention the most. As Coles et al (2019) noted, the effect size of onabotulinum-toxinA in comparison to placebo is large. Our work suggests an effect size of 1.09 is much larger than the effect size of 'facial feedback effects' in the 0.17-0.42 range and of antidepressants versus placebo trials equivalent to approximately 0.30 (Cipriani et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations